Educating Adolescent Reproductive Health and Sexuality through the Instagram Account @tabu.id - Sofian, Akhriyadi; Auliani, Nia; Ni'matul, Naili, Illiyun (Masyarakat: Jurnal Sosiologi, 2022)
The @tabu.id Instagram account presents itself as a channel for young internet users to obtain various information that are of significance to their lives as adolescents, including on topics of reproductive health and sexuality. Conducted using qualitative methods, this research utilized a virtual ethnographic (netnographic) approach. Data pertaining to @ tabu.id’s treatment of adolescent reproductive health and sexuality was obtained through a participatory observation of their Instagram account, as well as interviews with the co-founders, administrators, and followers. This study found that educating issues of reproductive health and sexuality to adolescents was more effectively carried out visually through social media, as it is the space they spend most of their time in. Recognizing Instagram being among the five digital applications most accessed by Indonesians, @ tabu.id has succeeded in educating adolescents by optimizing Instagram’s feed and story features to convey three major issues: puberty, dating violence, and Sexually-Transmitted Diseases (STDs).